Health-related quality of life results from the PRODIGE 5/ACCORD 17 randomised trial of FOLFOX versus fluorouracil–cisplatin regimen in oesophageal cancer. (October 2017) - Bascoul-Mollevi, C.; Gourgou, S.; Galais, M.-P.; Raoul, J.-L.; Bouché, O.; Douillard, J.-Y.; Adenis, A.; Etienne, P.-L.; Juzyna, B.; Bedenne, L.; Conroy, T.
Abstract: Background: A recent prospective randomised trial did not reveal significant differences in median progression-free survival between two chemoradiotherapy (CRT) regimens for inoperable non-metastatic oesophageal cancer patients. This secondary analysis aimed to describe the impact of CRT on health-related quality of life (HRQOL), physical functioning, dysphagia, fatigue and pain and to evaluate whether baseline HRQOL domains can predict overall survival. Patients and methods: A total of 267 patients were randomly assigned to receive with 50 Gy of radiotherapy in 25 fractions six cycles of FOLFOX or four cycles of fluorouracil and cisplatin on day 1. HRQOL was prospectively assessed using the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire version 3.0 with the oesophageal cancer module (QLQ-OES18). Results: Both groups showed high baseline compliance. Subsequently, compliance reduced to 41% at the 6-month follow-up. Baseline HRQOL scores showed no statistical differences between treatment arms. During treatment, both groups exhibited lower physical and social functioning and increased fatigue and dyspnoea, although dysphagia moderately improved in the fluorouracil–cisplatin arm only ( p = 0.047). During follow-up, HRQOL scores revealed no significant differences between chemotherapy regimens. Linear mixed model exhibited a treatment-by-time interaction effect for dysphagia ( p = 0.017) with a greater decrease in dysphagia in the fluorouracil–cisplatin group. Time until definitive deterioration analysis showed no significant differences in global HRQOL, functional or main symptom domains. However, time until definitive deterioration was significantly longer for the fluorouracil and cisplatin arm compared with FOLFOX for appetite loss ( p = 0.002), QLQ-OES-18 pain ( p = 0.008), trouble swallowing saliva ( p = 0.011) and trouble talking ( p = 0.020). Conclusion: Analyses of HRQOL scores revealed no statistically significant differences between patients with inoperable non-metastatic oesophageal cancer treated by FOLFOX versus those treated with a fluorouracil–cisplatin regimen as part of definitive CRT. Highlights: A longitudinal analysis of the health-related quality of life (HRQOL) data of the PRODIGE 5 randomised trial is proposed. The HRQOL longitudinal analysis was performed using a linear mixed model and time until definitive deterioration. The prognostic ability of baseline HRQOL domains for progression-free survival and overall survival were tested. Chemoradiotherapy significantly worsens fatigue, social and physical functions, with subsequent recovery from 24 weeks. Multivariate analysis confirmed the prognostic value of stage at diagnosis and possibly the baseline QLQ-OES18 EAT score.